Mangrove Conservation and Biodiversity Protection Strategies in Universitas Diponegoro to Achieve Net Zero Emission - Ambariyanto, Ambariyanto; Utama, Yos Johan; Sugianto, Denny Nugroho; Ariyanti, Dessy; Handayani, Elinna Putri (Universitas Diponegoro, 2023)
Indonesia is set the net zero emission target to be achieved by 2060. As part of that, Universitas Diponegoro (UNDIP) is committed to support the achievement of the goal by implementing several strategies. First is to reduce the amount of emission generated by the university daily activities, and second is boosting the activities of mangrove conservation and biodiversity protection. As UNDIP located in the northern part of Central Java, part of 108.000 kilometers coastline region of Indonesia, UNDIP prioritizes its academic activity and research focus on coastal region environmental and ecological development which enthuse the implementation of mangrove conservation and biodiversity protection. The strategy includes the structured mangrove and biodiversity conservation action directed by the University leaders, encouraging research and community service activities focusing on coastal region development and developing environmental-related curriculum for the students. In addition, UNDIP also supports research centers and students’ communities who focus on mangrove conservation, biodiversity protection, and coastal region development. By that, there are more than 50 types of flora in UNDIP land forest with carbon stock calculation up to 6,480.20 metric tons CO2 eq. Acc